Pemodelan Hujan–Debit dan Genangan 2D untuk Analisis Banjir pada DAS Buntung, Kabupaten Sidoarjo - Nur Izzah Elsa Nanda; Yang Ratri Savitri; Mahendra Andiek Maulana (Universitas Muhammadiyah Surabaya, 2026)
Flooding is the most frequent natural disaster in Indonesia, accounting for 55.07% of national disasters. Sidoarjo Regency, particularly Waru District, is highly vulnerable to flooding caused by the overflow of the Buntung River. Flood inundation in the area may persist for up to two days with water depths reaching 30–40 cm. Rapid development of residential, industrial, and transportation areas within the Buntung Watershed has reduced infiltration capacity, while high rainfall intensity, tidal fluctuations, and downstream channel constriction further aggravate flooding conditions. Therefore, the development of a flood inundation model is essential to support effective flood mitigation planning.This study aims to analyze flood characteristics and inundation distribution for selected return periods. Hydrological analysis was conducted using annual maximum rainfall data from 2013–2024. Areal rainfall was determined using the Thiessen Polygon method and frequency distribution analysis. Rainfall–runoff modeling was performed using HEC-HMS to estimate flood discharge, while 2D inundation modeling was carried out using HEC-RAS 2D. Sensitivity analyses of mesh size, computation interval, and model parameters were performed prior to calibration to obtain an optimal and computationally efficient configuration.The results show that a 30 m mesh size and a 10-second computation interval provide the optimal simulation configuration. The Manning parameter has the greatest influence on inundation extent and flood depth. Model calibration produced NSE values of 0,724 respectively, indicating good model performance. The simulation results show that the 10-year return period flood inundation is predominantly characterized by water depths of <10 cm, accounting for 26.32% of the inundated area, followed by depths of 10–20 cm (22.58%), 20–30 cm (17.38%), 30–50 cm (22.27%), and >50 cm (11.45%). The inundation with depths greater than 50 cm is predominantly distributed in the downstream area of the Buntung River, which is influenced by tidal conditions.